2021
DOI: 10.1061/(asce)st.1943-541x.0003025
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Modal Properties of an RC School Building during the 2016 Central Italy Seismic Swarm

Abstract: The terms and conditions for the reuse of this version of the manuscript are specified in the publishing policy. The use of copyrighted works requires the consent of the rights' holder (author or publisher). Works made available under a Creative Commons license or a Publisher's custom-made license can be used according to the terms and conditions contained therein. See editor's website for further information and terms and conditions. This item was downloaded from IRIS Università Politecnica delle Marche (http… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…A very low structural damping, calibrated through Rayleigh formulation as 𝜁𝜁 = 0.005 at the 1.30Hz and 5.45 Hz, equal to 𝛼𝛼 = 0.06595 for the mass-proportional coefficient and 𝛽𝛽 = 2.35785e − 04 for the stiffness-proportional coefficient is used. Small values of damping are consistent with the low amplitude of the seismic input(Gara et al, 2021), as further confirmed by the damping analysis performed on the recordings. Comparisons between the recordings and the simulated time-histories in acceleration and the related Fourier transforms are shown for each sensor in Figures11-14.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…A very low structural damping, calibrated through Rayleigh formulation as 𝜁𝜁 = 0.005 at the 1.30Hz and 5.45 Hz, equal to 𝛼𝛼 = 0.06595 for the mass-proportional coefficient and 𝛽𝛽 = 2.35785e − 04 for the stiffness-proportional coefficient is used. Small values of damping are consistent with the low amplitude of the seismic input(Gara et al, 2021), as further confirmed by the damping analysis performed on the recordings. Comparisons between the recordings and the simulated time-histories in acceleration and the related Fourier transforms are shown for each sensor in Figures11-14.…”
supporting
confidence: 76%
“…The epicentre of the first event (denominated Event 1) is 35 km far from the Bell Tower at a latitude of 38.1332 and longitude of 15.1643, with depth of the hypocentre of 10 km; the second event (indicated as Event 2) is located at latitude 38.1328 and longitude 15.9537, 35 km away from the Bell Tower and hypocentre depth of 14 km.The time-histories recorded at the foundation (Sensor 1) are used as seismic inputs applied at the same location in the finite element model including the soil underneath as prescribed accelerations, rather than applied to the bedrock after a pertinent back propagation. It is worth emphasising that the signals on the 3 principal directions, recorded at the base do not correspond to the free-field seismic motion at the building location, owing to kinematic and inertial soil-structure interaction effects(Gara et al 2021), hence, they cannot be applied at the soil bedrock as conventional done in soil-structure interaction analyses. Therefore, the input acceleration time-histories about the 3 principal directions, 𝑢𝑢̈𝑥𝑥, 𝑢𝑢̈𝑦𝑦, and 𝑢𝑢̈𝑧𝑧, are exactly those from the recordings at foundation level, depicted in Figure11.…”
mentioning
confidence: 99%
“…The accuracy of the identified model in reproducing the building response is evaluated comparing the predicted and measured time histories of accelerations through the comparison metrics proposed by Kavrakov et al [20], which consider several signal properties such as phase, peak, root mean square, and frequency contents. A detailed explanation of the approach can be found in Gara et al (2021) [21].…”
Section: Description Of the Linearization Proceduresmentioning
confidence: 99%
“…However, although this strategy is widely recognised to be of useful application, a relatively low number of works can be found dealing with applications on real or scaled structures. Some authors performed vibration-based tests on real buildings during the gradual artificially induced damage to both structural and non-structural components [5][6][7] or due to earthquakes, [8,9] while others investigated the modal property evolutions of laboratory specimens representative of Reinforced Concrete (RC), [10][11][12][13][14] steel, [15,16] and steel-concrete composite structures [4,17] subjected to displacements and forces such as to produce structural and non-structural damage. However, a lack of works dealing with damage evaluation of infilled structures by using vibration-based techniques can be observed in the literature.…”
Section: Introductionmentioning
confidence: 99%